Selective isolation of hydrophobin SC3 by solid-phase extraction with polytetrafluoroethylene microparticles and subsequent mass spectrometric analysis - Kupčík, Rudolf; Zelená, Miroslava; Řehulka, Pavel; Bílková, Zuzana; Česlová, Lenka (Journal of separation science, 2016)
Hydrophobins are small proteins that play a role in a number of processes during the filamentous fungi growth and development. These proteins are characterized by the self-assembly of their molecules into an amphipathic membrane at hydrophilic-hydrophobic interfaces. Isolation and purification of hydrophobins generally present a challenge in their analysis. Hydrophobin SC3 from Schizophyllum commune was selected as a representative of class I hydrophobins in this work. A novel procedure for selective and effective isolation of hydrophobin SC3 based on solid-phase extraction with polytetrafluoroethylene microparticles loaded in a small self-made microcolumn is reported. The tailored binding of hydrophobins to polytetrafluoroethylene followed by harsh elution conditions resulted in a highly specific isolation of hydrophobin SC3 from the model mixture of ten proteins. The presented isolation protocol can have a positive impact on the analysis and utilization of these proteins including all class I hydrophobins. Hydrophobin SC3 was further subjected to reduction of its highly stable disulfide bonds and to chymotryptic digestion followed by mass spectrometric analysis. The isolation and digestion protocols presented in this work make the analysis of these highly hydrophobic and compact proteins possible.
Keywords: mléko; disulfidy; bromelainy; Polytetrafluoroethylene; proteomika; thermolysin; chymotrypsin; karboanhydrasy; albuminy; Disulfides; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; cytochromy c; Schizophyllum; Mass Spectrometry; kaseiny; skot; Carbonic Anhydrases; Caseins; Hydrophobin SC3; kur domácí; Chymotrypsin; Concanavalin A; Horses; extrakce na pevné fázi; Thermolysin; Canavalia; Albumins; Erythrocytes; Proteomics; Chickens; myokard; zvířata; erytrocyty; Humans; Ananas; Microspheres; koně; Myocardium; Tandem Mass Spectrometry; Isolation; Mass spectrometry; Cattle; Milk; Protein analysis; polytetrafluoroethylen; konkanavalin A; spektrometrie hmotnostní - ionizace laserem za účasti matrice; tandemová hmotnostní spektrometrie; Cytochromes c; Bromelains; ananasovník; mikrosféry; hmotnostní spektrometrie; Polytetrafluoroethylene microparticles; lidé; Solid Phase Extraction; Animals